دور المنهج التّواصلي في تعلّم اللّغة عن طريق دروس فهم المنطوق و إنتاجه - السّنة الثانية من التّعليم المتوسّط أنموذجا - - ضاوي, فوزية; بن فضة, فريدة (جامعة الوادي - University of Eloued, 2021)
لقد سعت عدّة مناهج إلى تيسير طرق و كيفيّات تعلّم لغة من اللّغات و تعليمها ، لكنّ كلّ منهج منها كان يحمل من النّقائص و يتلقّى من الانتقادات ما يجعله عاجزا عن تحقيق الأهداف التّعليميّة المسطّرة. و بتطوّر الدّراسات وتنوّع الأنشطة التّعليميّة ، ظهرت الحاجة إلى تبنّي منهج يعطي الحرّيّة للمتعلّم أثناء محاولته تعلّم لغة ما عن طريق التّواصل الشفاهي كما هو الحال في نشاط فهم المنطوق و إنتاجه ،ومن خلال هذه الدّراسة سنحاول رصد أهميّة التّواصل المستمر داخل وضعيات تعليميّة تعلّميّة في تسهيل طرق التّعبير الشفاهي عن الأحاسيس و الآراء ، وبالتّالي إثراء الرّصيد اللّغوي للمتعلّمين . Abstract:Several curricula have sought to facilitate ways and means of learning and teaching a language, but each syllabus has been imperfect and has received criticism that makes it unable to achieve the educational goals laid down. With the evolution of studies and the diversity of educational activities, the need has emerged to adopt a curriculum that gives freedom to the learner as he attempts to learn a language through transparent communication, as in the case of the activity of understanding and producing the operative, and through this study we will try to monitor the importance of continuous communication within learning settings in facilitating transparent expression of feelings and opinions, thereby enriching the linguistic balance of learners.
The role of the communication curriculum in language learning through thelessons of understanding the operative. -Second year average model -
مقال
Keywords: منهج تواصلي ، اكتساب لغة ، فهم منطوق و إنتاجية ، تعبير شفاهي; learning a lanquage, continuous communication , educational goals, evolution of studies.